Voluntary export restraints in a trade model with sticky price: Linear and nonlinear feedback solutions - Luca Lambertini; Arsen Palestini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2017)
We revisit the adoption of voluntary export restraints (VERS) in the differential Cournot game with sticky price and intraindustry trade by Dockner and Haug (1991). The analysis relies on linear and nonlinear feedback strategies, to encompass the special cases considered in Fujiwara (2010) and to show that a VER may arise in correspondence of any free trade equilibrium generated by feedback information such that competition is at least as strong as under open-loop rules. This result can be interpreted in the light of the dynamic formulation of conjectural variations due to Dockner (1992).
Keywords: C73; D43; F12; L13; 330; differential games; intraindustry trade; VER; conjectural variations